Persepsi Guru Terhadap Pembelajaran Daring pada Masa Pandemi Covid-19 di Sekolah Dasar Negeri 1 Tajemsari - Kurnia Gusti Ditananda; Mira Azizah; Intan Rahmawati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to analyze teacher perceptions of online learning and the implementation of online learning in SD Negeri 1 Tajemsari. This study uses a qualitative approach. The research data sources consist of informants and documents collected through in-depth interviews, documentation and observation techniques. The data validity technique used is source triangulation. The results showed that teacher perceptions were formed through the teacher's process of seeking information about online learning, adapting to online learning, and evaluating the implementation of online learning. The teacher's perception of online learning is influenced by the teacher's experience. This also affects the way teachers implement online learning in elementary schools. The implementation of online learning consists of planning, implementation, and assessment. Teachers have not been able to carry out learning according to process standards. The learning methods used vary according to the teacher's perspective on online learning.